Differential Pressure Flow Transmitter Type Azbil JTD920S Performance Analysis in Desalination Process at PT Indonesia Power UBP Cilegon - Muhamad Aldi Firdaus; Diyajeng Luluk Karlina; Yudi Nugraha (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The Gas and Steam Power Plant (PLTGU) utilizes exhaust heat from gas turbines to produce steam, which is then used to drive steam turbines. One of the critical processes in this system is seawater desalination, which requires reliable measuring instruments to ensure the continuity and quality of the water supply. The Differential Pressure Flow Transmitter type Azbil JTD920S is used to measure fluid flow rates at four main points: Sea Water Flow (feed), Distillate Water Flow, Condensate Water Flow, and Sea Water to Ejector Condenser Flow. A decline in transmitter performance may occur due to environmental factors, corrosion, and high workload, making periodic preventive maintenance (PM) essential. This study aims to analyze the transmitter’s performance by comparing PM data with the manufacturer’s maximum specifications using literature studies, direct observation, and interviews. The calculation results show that the highest performance levels are found in the Distillate Water Flow (73.53%) and Sea Water to Ejector Condenser Flow (73.87%) lines, while the lowest is in the Condensate Water Flow (49.00%). These findings emphasize the importance of close monitoring of high-performance transmitters to prevent premature failure and maintain the efficiency of the desalination process.